Factors predicting outcomes of anterior cervical discectomy and fusion in cervical spondylotic myelopathy: A prospective study - Chutima Chaichuangchok (2018)
© 2017, Medical Association of Thailand. All rights reserved. Background: Cervical spondylotic myelopathy (CSM) is a common condition in elderly. Anterior cervical discectomy and fusion (ACDF) becomes a standard procedure to address the ventral spinal cord compression from degenerated disc and osteophyte. However, the results after treatment are dubitable in many patients. There are many factors associated with the outcomes after surgery. Objective: To investigate the predictive factors for the outcomes of ACDF in patient with CSM. Material and Method: This prospective study was conducted between March 2011 and August 2013, all patients with clinical diagnosis of CSM who underwent ACDF by a neurosurgeon, were enrolled in the study. Recorded details included background factors, patient factors and operative factors. The Japanese Orthopaedic Association (JOA) score was used to evaluate preoperative and postoperative neurological status. Results: Fivety-four patients (35 males and 19 females) with mean age of 59 years old were included in the study. Mean duration of preoperative symptoms was 10.2 months. Regarding the JOA score, 45 patients (83.3%) had improvement, whereas 9 (16.7%) had no improvement. Regarding predictive factors, there was no statistically significant difference in age, gender, duration of symptom, underlying disease, smoking, number of ACDF level and type of bone graft between the groups with and without improvement of JOA score. Conclusion: There was no single factor could predict the operative outcomes. Nonetheless, male gender, patients without underlying disease and preoperative symptoms less than 1 year are the factors that are convincingly considered to be the favorable prognosticators.